Non‐invasive assessment of culture media from goat cloned embryos associated with subjective morphology by gas chromatography – mass spectroscopy‐based metabolomic analysis. (18th August 2017) - Zhang, Yan‐Li; Zhang, Guo‐Min; Jia, Ruo‐Xin; Wan, Yong‐Jie; Yang, Hua; Sun, Ling‐Wei; Han, Le; Wang, Feng
Abstract: Pre‐implantation embryo metabolism demonstrates distinctive characteristics associated with the development potential of embryos. We aim to determine if metabolic differences correlate with embryo morphology. In this study, gas chromatography – mass spectroscopy (GC‐MS)‐based metabolomics was used to assess the culture media of goat cloned embryos collected from high‐quality (HQ) and low‐quality (LQ) groups based on morphology. Expression levels of amino acid transport genes were further examined by quantitative real‐time PCR. Results showed that the HQ group presented higher percentages of blastocysts compared with the LQ counterparts ( P  <   0.05). Metabolic differences were also present between HQ and LQ groups. The culture media of the HQ group showed lower levels of valin, lysine, glutamine, mannose and acetol, and higher levels of glucose, phytosphingosine and phosphate than those of the LQ group. Additionally, expression levels of amino acid transport genes SLC1A5 and SLC3A2 were significantly lower in the HQ group than the LQ group ( P  <   0.05, respectively). To our knowledge, this is the first report which uses GC‐MS to detect metabolic differences in goat cloned embryo culture media. The biochemical profiles may help to select the most in vitro viable embryos.